2011
DOI: 10.2500/ajra.2011.25.3660
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Aspirin Hypersensitivity in Patients with Nasal Polyposis and Contributing Factors

Abstract: ASA hypersensitivity is quite common in patients with NP. Patients with extensive and long-term NP with multiple polyp operations require evaluation for the presence of ASA hypersensitivity in terms of chronic management and future risks of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Respiratory symptoms are less likely to be associated with other types of NSAID hypersensitivity. Our study confirmed that NSAID‐induced respiratory reactions are more prevalent among patients with asthma and/or chronic rhinosinusitis suggesting that NERD type of hypersensitivity could be most likely diagnosed in these patients. Although respiratory symptoms of NSAID hypersensitivity are usually considered to be a component of the ‘aspirin triad’, in our study only 15% of the patients complaining of breathing difficulties after NSAIDs had coexisting asthma and rhinosinusitis and more than half have not reported neither upper nor lower respiratory tract disorders.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Respiratory symptoms are less likely to be associated with other types of NSAID hypersensitivity. Our study confirmed that NSAID‐induced respiratory reactions are more prevalent among patients with asthma and/or chronic rhinosinusitis suggesting that NERD type of hypersensitivity could be most likely diagnosed in these patients. Although respiratory symptoms of NSAID hypersensitivity are usually considered to be a component of the ‘aspirin triad’, in our study only 15% of the patients complaining of breathing difficulties after NSAIDs had coexisting asthma and rhinosinusitis and more than half have not reported neither upper nor lower respiratory tract disorders.…”
Section: Discussionsupporting
confidence: 79%
“…Most studies published earlier assessed the prevalence of aspirin/NSAID‐induced respiratory symptoms in selected populations of asthmatics and/or patients with chronic rhinosinusitis (CRS), which is compatible with the diagnosis of type I hypersensitivity (NERD), previously called ‘aspirin triad’ . The prevalence of respiratory type of hypersensitivity to NSAIDs depended on the population sampled was higher among patients with asthma , patients with rhinosinusitis and nasal polyposis and seemed to be more prevalent among more severe asthmatics . Only few studies analyzed the prevalence of NSAID‐induced hypersensitivity in the general population, and these recruited patients only in single countries .…”
mentioning
confidence: 99%
“…This is in contrast to other definitions where AERD was used to refer to patients with asthma and intolerance to COX-1 inhibitors but not necessarily chronic sinus disease or nasal polyps, 13, 15, 3235 or to patients who had nasal polyps and COX-1 inhibitor intolerances but not necessarily asthma 36 . Given the lack of universally accepted terminology and definitions, it is common for the same diagnosis ( i.e.…”
Section: Discussionmentioning
confidence: 93%
“…ECRS has significantly higher association with asthma and higher incidence of aspirin sensitivity 13,14 . In our study, bronchial asthma and aspirin sensitivity were found to be more common in patients with eosinophilic polyps; the association of bronchial asthma and eosinophilic polyps was weak; and no significant statistical association between eosinophilic polyps and aspirin sensitivity.…”
Section: Sakuma Et Al Concluded That Blood Eosinophilia Asthma Complmentioning
confidence: 94%